Does foreign direct investment affect growth in MENA countries? A semi-parametric fixed-effects approach. Issue 1 (2nd January 2020) - Ben Jelili, Riadh
ABSTRACT: It is often asserted with confidence that foreign direct investment (FDI) is beneficial for economic growth, especially in the host developing economy. Nevertheless, there is no empirical consensus on a positive effect of FDI on host-country growth, nor on the direction of causation. One of the reasons behind the lack of consensus is likely the presence of nonlinearities in the FDI and growth relationship. Most of the previous studies either used the linear empirical growth model or tried to bypass the nonlinearity issue by using ad hoc procedures. However, it is also true that growth theory provides little guidance about the exact nature of nonlinearity. Consequently, it is almost impossible to determine the exact form of nonlinear specification that would be appropriate for all data sets and data ranges. The paper investigates this challenging question in empirical growth literature that is the impact of FDI in promoting economic growth in developing economies without adopting any ad hoc procedure to capture the nonlinearity in the FDI–growth relationship. Based on a dualistic growth framework and a partial linear regression approach, it is possible to separate measures for sector externality and factor productivity effects between the two sectors (exports and non-exports sector). Sectoral externality is defined as a function of real FDI stocks per capita. Thereby, the adopted theoretical framework allows capturing both direct and indirect effects of FDI on economic growth across eight MENA countries during the period 1990–2016.